2011
DOI: 10.1115/1.4005225
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Forceps for Use in Endoscopic Surgery—Initial Design, Prototype, and Testing

Abstract: This paper presents a 3.0 mm diameter multifunctional endoscopic forceps design for use in minimally invasive flexible endoscopic surgical procedures. Multifunctional capabilities including grasping, spreading, and cauterizing tissue are demonstrated experimentally and compared to commercially available forceps. Models of the proposed design predict considerable improvements in opening range (140%) and force application (87%) for both grasping and spreading when compared to currently used endoscopic forceps. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Studies had shown the advantages of minimal access procedures compared to open conventional ones. The reduction in surgical invasiveness results in reductions of procedure time, post-operation pain, trauma, blood-loss, recovery time and risk of infection [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies had shown the advantages of minimal access procedures compared to open conventional ones. The reduction in surgical invasiveness results in reductions of procedure time, post-operation pain, trauma, blood-loss, recovery time and risk of infection [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The change of the mecha- In this study described above, calibrated forceps had variable or uncontrolled contact surfaces, despite intentions to incorporate such control for constant contact surface area [7,8]. One solution to this problem would be to attach a xed, round, smooth slug to the tip of each arm of the forceps, thus ensuring a constant contact area [9].…”
Section: Introductionmentioning
confidence: 99%